A relational approach to co-create Advance Care Planning with and for people living with dementia: a narrative study - Tharin Phenwan; Judith Sixsmith; Linda McSwiggan; Deans Buchanan (BMC Palliative Care)
Abstract Background Discussing Advance Care Planning (ACP) with people living with dementia (PwD) is challenging due to topic sensitivity, fluctuating mental capacity and symptom of forgetfulness. Given communication difficulties, the preferences and expectations expressed in any ACP may reflect family and healthcare professional perspectives rather than the PwD. Starting discussions early in the disease trajectory may avoid this, but many PwD may not be ready at this point for such discussions. Consequently, the optimal timing to discuss an ACP with and for PwD is undetermined. This study explored the changing needs of PwD and experiences of social contexts that influence ACP initiation and revision and aimed to identify the optimal time to discuss an ACP with PwD. Methods Narrative online and telephone interviews were conducted with 13 PwD and 23 family carers. Participants were recruited via the Join Dementia Research (JDR) Platform. Narrative analysis was used to identify patterns in the data, generating three narratives: Shifting Expectations; Relational Interdependency and Trigger Points. Results The Shifting Expectations narrative indicated that PwD’s needs shifted to co-constructed needs with their family as PwD’s independence declined. This was reflected in the Relational interdependency narrative where PwD almost always co-created and revised their ACPs with trusted key persons who provided relational support. The Trigger points narrative indicated various points in time when PwD can effectively initiate and revise their ACPs, ranging from before the diagnosis to years afterwards, challenging the current suggestion of an early ACP initiation. Conclusions This study highlighted the changing co-constructed needs between PwD and their families that influence how PwD initiate and revise their ACP. The identification of ACP trigger points - the pivotal events throughout the dementia journey - that prompt PwD and family members to discuss their ACPs were suggested, indicating that PwD can initiate and revise their ACPs throughout the disease trajectory provided relational support is available whereby key persons involved in their care are involved and agree with the decisions being made. Therefore, an alternative, relational approach to ACP with and for PwD is recommended.